Good practices in funding transdisciplinary and participatory research for sustainable development in Africa: Learning lessons from German public funding programmes on sustainable land management and agricultural development in Africa - Eefje Aarnoudse; Tina Beuchelt; Berenice Fischer; Hannah Jaenicke; Wiltrud Terlau (Hochschule Bonn-Rhein-Sieg, Internationales Zentrum für Nachhaltige Entwicklung (IZNE), 2024)
This working paper explores how funding requirements enable transdisciplinary research (TDR) for sustainable development in Africa, focusing on German public funders and their TDR programmes in sustainable land management and agricultural development. It consolidates experiences from Global North-South collaborations to identify good practices in funding TDR, particularly during the initial phase of defining research problems and objectives. Key findings suggest that funders should combine research and development funding for long-term TDR processes, explicitly define TDR expectations in selection processes, create TDR-friendly budget structures, and support a collaborative problem definition phase by funding joint proposal writing and facilitating joint learning. The paper aims to foster a dialogue on good practices in funding TDR between funders, researchers, and practice organizations in Germany and Africa, facilitated by a series of workshops under the INTERFACES project. Insights are based on key expert interviews and the first workshop with funders and researchers in Germany.
urn:nbn:de:hbz:1044-opus-86490
Keywords: 650; research funding; transdisciplinary research; Global North-South collaboration; Africa